"Natural allies": Librarians, archivists, and big data in international digital humanities project work. Issue 4 (9th July 2018) - Poole, Alex H.; Garwood, Deborah A.
Abstract : Purpose: In Digging into Data 3 (DID3) (2014-2016), ten funders from four countries (the USA, Canada, the UK, and the Netherlands) granted $5.1 million to 14 project teams to pursue data-intensive, interdisciplinary, and international digital humanities (DH) research. The purpose of this paper is to employ the DID3 projects as a case study to explore the following research question: what roles do librarians and archivists take on in data-intensive, interdisciplinary, and international DH projects? Design/methodology/approach: Participation was secured from 53 persons representing eleven projects. The study was conducted in the naturalistic paradigm. It is a qualitative case study involving snowball sampling, semi-structured interviews, and grounded analysis. Findings: Librarians or archivists were involved officially in 3 of the 11 projects (27.3 percent). Perhaps more importantly, information professionals played vital unofficial roles in these projects, namely as consultants and liaisons and also as technical support. Information and library science (ILS) expertise helped DID3 researchers with issues such as visualization, rights management, and user testing. DID3 participants also suggested ways in which librarians and archivists might further support DH projects, concentrating on three key areas: curation, outreach, and ILS education. Finally, six directions for future research are suggested. Originality/value: Much untapped potential exists for librarians and archivists to collaborate with DH scholars; a gap exists between researcher awareness and information professionals' capacity.